Penerapan Pendidikan Karakter Berbasis Kearifan Lokal - rosmalah rosmalah (Universitas Negeri Makassar, 2021)
Abstract. This study aims to describe the application of character education based on local wisdom in schools. The method used is descriptive qualitative with a case study approach. Data obtained through in-depth interviews, participant observation, and document study. The results show that the implementation of character education can be done by: (1) integration in learning subjects, (2) interaction in the school environment between teachers and students and students with students, and (3) role models from teachers in the school environment, and (4) ) self-development activities. The value of local wisdom applied, namely Siri means: shame, tabe 'means excuse me and sorry, sipakatau means humanizing each other, sipakainge means reminding each other so that each individual should avoid deviant actions, and sipakalebbi means respecting and praising one another.